TOOLSTIBS: A decision-making tool for IBS product selection / Mohd Rofdzi Abdullah ... [et al.] - Abdullah, Mohd Rofdzi; Mohd Pahroraji, Mohamad Ezad Hafez; Abd Rashid, Mohd Najib; Wan Mohammad, Wan Nur Syazwani (2024)
The Malaysian construction industry is often associated with the infamous problems of being Dirty, Difficult and Dangerous (3D). To support efforts in providing solutions to the issues, an innovative strategy known as the Industrial Building System (IBS) was successfully developed. Presently, the manufacturers and producers of IBS have incorporated a multitude of advantages and benefits into their products. However, selecting the appropriate type of IBS product for construction projects was identified as a critical issue in the decision-making process at the conceptual stage. It could be overwhelming for the decision maker to decide on an IBS product due to the vast selection criteria that need to be considered. Therefore, a tool is required to facilitate and assist in the efficient decision-making associated with selecting the type of IBS product. The consideration criteria are structure and materials' design, site orientation, safety, client perspectives, environmental issues and sustainability, organisational issues, and risk. To overcome this issue, a tool known as TOOLSTIBS was developed using prominent Microsoft Excel. The tool has the capability to determine priority for product selection, provide quantitative analysis in suggestions when two equally weighting factors are involved, and facilitate the person in charge of the decision-making process. The advantages of TOOLSTIBS include serving as an alternative to existing expert choice apps in the current market, incorporating forty main criteria related to IBS systems, and comparing three IBS products for recommendations.